Implementasi Media Roda Berputar dan Media Digital Canva dalam Pembelajaran Pak di SMKS Tarung Riwut - Tina Tina; Gabriel Stefanofit Akwan; Wandi Wandi; Cindi Anisa Bahar; Lelo Lelo; Matius Timan Herdi Ginting (Lembaga Pengembangan Kinerja Dosen, 2025)
Learning media is an important component in the teaching and learning process because it functions as a tool to convey information that can stimulate students' interest, attention, and understanding of the material. The implementation of rotating wheel media and Canva digital media in Christian Religious Education (PAK) learning at SMKS Tarung Riwut has been proven to be able to create a more interactive, enjoyable, and contextual learning atmosphere. The rotating wheel media provides a learning experience that is direct, competitive, and actively involves all students, so it is very effective in increasing student involvement and understanding of Christian teaching values. Meanwhile, Canva digital media provides a creative and visual expression space that allows teachers and students to design learning materials with an attractive and easy appearance. This study uses a qualitative approach with a descriptive method, which aims to describe in depth the process of implementing rotating wheel media and Canva digital media in Christian Religious Education (PAK) learning at SMKS Tarung Riwut. Data were collected through observation, interview, and documentation techniques. Observations were carried out during the learning process to find out how the two media were applied by the teacher and responded to by the students. Interviews were conducted with PAK teachers and several students to explore perceptions, experiences, and benefits felt during the use of the media. It is understood, in line with the demands of 21st century learning.